2020
DOI: 10.1186/s12909-020-02005-8
|View full text |Cite
|
Sign up to set email alerts
|

Training in obstetric and neonatal emergencies in Mexico: effect on knowledge and self-efficacy by gender, age, shift, and profession

Abstract: Background: Continuing education is essential for healthcare workers. Education interventions can help to maintain and improve competency and confidence in the technical skills necessary to address adverse events. However, characteristics of the health provider such as age (related to more critical and reflexive attitude); sex (relationship with gender socialization), profession and work conditions might have an influence on the effect of continuing education efforts. Methods: A training in the management of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Since the 1990s, it has been reported that the main reason why women do not like obstetric attention in public health institutions in Mexico was the perception of poor care, mistreatment and lack of trust in staff. 13 Recently another study 14 documented that health personnel reported a lack of constant training and the fear of possible legal claims by users or adverse legal situations due to complications during obstetrics as the main reason for not attending births.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, it has been reported that the main reason why women do not like obstetric attention in public health institutions in Mexico was the perception of poor care, mistreatment and lack of trust in staff. 13 Recently another study 14 documented that health personnel reported a lack of constant training and the fear of possible legal claims by users or adverse legal situations due to complications during obstetrics as the main reason for not attending births.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is needed The reduction in CB was similar to that found for PRONTO (Programa de Rescate Obstétrico y Neonatal, Tratamiento Óptimo y Oportuno), an obstetric and neonatal emergency management program evaluated in Mexico, with which AMBAR shares similarities. 10,18,19,25,50 It is likely that the decrease is caused by increased provider confidence in handling complications that can arise during low-risk deliveries, without resorting to an unnecessary "emergency" CB, as well as to an emphasis on humanized birth care. 25,50…”
Section: Discussionmentioning
confidence: 99%
“…We collected information on covariates that were previously found to influence birth practices themselves or knowledge and self-efficacy on birth practices in Mexico. 10,18,19,45 Health provider covariates included profession, gender, and previous training in birth care. Maternal covariates included schooling, speaking an indigenous language, and the number of previous pregnancies.…”
Section: Covariatesmentioning
confidence: 99%
See 2 more Smart Citations